Direct sensing of endothelial oxidants by vascular endothelial growth factor receptor-2 and c-Src. - Monica Lee; Wing C Choy; Md Ruhul Abid (PLoS ONE, 2011)
BACKGROUND: ADPH oxidase-derived reactive oxygen species (ROS) play important roles in redox homeostasis and signal transduction in endothelial cells (ECs). We previously demonstrated that c-Src plays a key role in VEGF-induced, ROS-dependent selective activation of PI3K-Akt but not PLCγ-1-ERK1/2 signaling pathways. The aim of the present study was to understand how VEGFR-2-c-Src signaling axis 'senses' NADPH oxidase-derived ROS levels and couples VEGF activation of c-Src to the redox state of ECs. METHODOLOGY/PRINCIPAL FINDINGS: Using biotinylated probe that detects oxidation of cysteine thiol (cys-OH) in intracellular proteins, we demonstrate that VEGF induced oxidative modification in c-Src and VEGFR-2, and that reduction in ROS levels using siRNA against p47(phox) subunit of Rac1-dependent NADPH oxidase inhibited this phenomenon. Co-immunoprecipitation studies using human coronary artery ECs (HCAEC) showed that VEGF-induced ROS-dependent interaction between VEGFR-2 and c-Src correlated with their thiol oxidation status. Immunofluorescence studies using antibodies against internalized VEGFR-2 and c-Src demonstrated that VEGF-induced subcellular co-localization of these tyrosine kinases were also dependent on NADPH oxidsase-derived ROS. CONCLUSION/SIGNIFICANCE: These results demonstrate that VEGF induces cysteine oxidation in VEGFR-2 and c-Src in an NADPH oxidase-derived ROS-dependent manner, suggesting that VEGFR-2 and c-Src can 'sense' redox levels in ECs. The data also suggest that thiol oxidation status of VEGFR-2 and c-Src correlates with their ability to physically interact with each other and c-Src activation. Taken together, these findings suggest that prior to activating downstream c-Src-PI3K-Akt signaling pathway, VEGFR-2-c-Src axis requires an NADPH oxidase-derived ROS threshold in ECs.